Differential effects of 10-Hz and 40-Hz transcranial alternating current stimulation (tACS) on endogenous versus exogenous attention. Issue 2 (3rd April 2017) - Hopfinger, Joseph B.; Parsons, Jonathan; Fröhlich, Flavio
ABSTRACT: Previous electrophysiological studies implicate both alpha (8–12 Hz) and gamma (>30 Hz) neural oscillations in the mechanisms of selective attention. Here, participants preformed two separate visual attention tasks, one endogenous and one exogenous, while transcranial alternating current stimulation (tACS), at 10 Hz, 40 Hz, or sham, was applied to the right parietal lobe. Our results provide new evidence for the roles of gamma and alpha oscillations in voluntary versus involuntary shifts of attention. Gamma (40 Hz) stimulation resulted in improved disengagement from invalidly cued targets in the endogenous attention task, whereas alpha stimulation (10 Hz) had no effect on endogenous attention, but increased the exogenous cuing effect. These findings agree with previous studies suggesting that right inferior parietal regions may be especially important for the disengagement of attention, and go further to provide details about the specific type of oscillatory neural activity within that brain region that is differentially involved in endogenous versus exogenous attention. Our results also have potential implications for the plasticity and training of attention systems.